Epidemiology of reported cases of leptospirosis in the EU/EEA, 2010 to 2021 - Beauté, Julien; Innocenti, Francesco; Aristodimou, Aristos; Špačková, Michaela; Eves, Caroline; Kerbo, Natalia; Rimhanen-Finne, Ruska; Picardeau, Mathieu; Faber, Mirko; Dougas, Georgios; Halldórsdóttir, Anna Margrét; Jackson, Sarah; et al. (Euro surveillance, 2024)
BackgroundLeptospirosis is a zoonotic disease caused by bacteria of the genus Leptospira. Humans are infected by exposure to animal urine or urine-contaminated environments. Although disease incidence is lower in Europe compared with tropical regions, there have been reports of an increase in leptospirosis cases since the 2000s in some European countries.AimWe aimed to describe the epidemiology of reported cases of leptospirosis in the European Union/European Economic Area (EU/EEA) during 2010-2021 and to identify potential changes in epidemiological patterns.MethodsWe ran a descriptive analysis of leptospirosis cases reported by EU/EEA countries to the European Centre for Disease Prevention and Control with disease during 2010-2021. We also analysed trends at EU/EEA and national level.ResultsDuring 2010-2021, 23 countries reported 12,180 confirmed leptospirosis cases corresponding to a mean annual notification rate of 0.24 cases per 100,000 population. Five countries (France, Germany, the Netherlands, Portugal and Romania) accounted for 79% of all reported cases. The highest notification rate was observed in Slovenia with 0.82 cases per 100,000 population. Overall, the notification rate increased by 5.0% per year from 2010 to 2021 (95% CI: 1.2-8.8%), although trends differed across countries.ConclusionThe notification rate of leptospirosis at EU/EEA level increased during 2010-2021 despite including the first 2 years of the COVID-19 pandemic and associated changes in population behaviours. Studies at (sub)national level would help broaden the understanding of differences at country-level and specificities in terms of exposure to Leptospira, as well as biases in diagnosis and reporting.
Keywords: Leptospirosis; Evropská unie; Evropa; leptospiróza; Romania; Rumunsko; European Union; Leptospira; Pandemics; Humans; pandemie; Europe; Epidemiology; lidé; Surveillance